Of squalls and mutinies: emergency politics and black democracy in Moby-Dick and 'The Heroic Slave'. Issue 11 (2nd November 2021) - Spengler, Nicholas
ABSTRACT: This article takes an object-oriented approach to the analogies between weather events and political events in Herman Melville's Moby-Dick (1851) and Frederick Douglass's 'The Heroic Slave' (1853), arguing that marine weathers in these maritime fictions take the measure of the political without being reducible to it. I integrate political-ecological theories of emergency and 'emergence' with the analogic poetics of both object-oriented philosophy and critical race studies to show how stormy weather in these texts carries a special charge in articulating an emergent politics of Black democracy.